Critical care nurses’ experiences on dishonesty: A qualitative content analysis - Negarandeh, Reza (Nursing ethics, 2022)
Background:Providing information to patients is an essential aspect of care. The way in which such information is transmitted is also important and is affected by different variables. The perceptions of dishonest nursing staff have not been sufficiently discussed to date.Aim:The purpose is to explore the reasons for dishonesty in transmitting information to patients.Design and Method:In this qualitative content analysis study, data were collected using semi-structured interviews with Twelve Iranian Critical Care Nurses from January 2020 till August 2020. Data were analyzed according to Graneheim and Lundman approach.Ethical consideration:The research protocol was authorized by the Ethics Committee of the Medical Sciences University of Tehran (Register number: 95-04-99-33485).Results:The findings indicated that dishonesty in giving information to the patients has many reasons. Although lying is not compatible with ethical care, working conditions sometimes forced nurses to hide the truth.Discussion and conclusion:Nurses believed honesty was an integral aspect of professional practice, but situational specifics have an effect on whether the truth is told or withheld. Finally, the nurses noticed a big gap between what they want to tell and what they were doing in practice.